Guidance and the Filipino youth-in-conflict with the law - Hernandez, Christopher Perez (2007)
Juvenile crime and delinquency are lingering problems in every society today. This study was conceptualized to established a profile of the Filipino youth-in-conflict with the law and posits that Guidance, as a helping profession, has a unique role in helping them. Psychological tests were administered, analyzed and interpreted to all the participants, focus group discussions were also conducted, and a prototype Guidance program was proposed and tried out. Conclusions inferred that delinquency is a product of the interplay of various factors including psychological attributes, family dynamics, school experiences, community influences, and spiritual well-being.